Genomics knowledge and equity: a global public goods perspective of the patent system - Smith Richard D.; Thorsteinsdóttir Halla; Daar Abdallah S.; Gold E. Richard; Singer Peter A. (The World Health Organization, 2004)
Genomics, the comprehensive examination of an organism's entire set of genes and their interactions, will have a major impact on the way disease is diagnosed, prevented and treated in the new millennium. Despite the tremendous potential it holds for improving global health, genomics challenges policy-makers to ensure that its benefits are harnessed equitably across populations and nations. The classification of genomics as a global public good and the inequity encountered in the development and application of genomics knowledge are outlined in this paper. We examine the effect of the current patent system on the distribution of costs and benefits relating to genomics knowledge between countries of different economic strength. The global public goods concept provides a normative economic rationale for the modification of certain aspects of the current patent system and for the creation of complementary mechanisms to respond to the health needs of low-income and middle-income countries.